The role of neuroendocrine differentiation in treatment resistance of prostate cancer and intervention strategies - Wang, Baozhen; Zhang, Yanyun; Zhang, Wenbo (Frontiers in Oncology, 2026)
Prostate cancer is one of the most common malignancies in men, and resistance to conventional treatments is frequently encountered in clinical practice. Among the mechanisms contributing to this resistance, neuroendocrine differentiation (NED) is particularly significant. NED does not only change the basic biological characteristics of cancer cells but also is capable of inducing resistance to endocrine therapy and chemotherapy, which impact the overall prognosis negatively. While NED drives prostate cancer progression and treatment resistance, its pathophysiology and the mechanisms underlying its development are still poorly understood, which restricts the availability of effective clinical interventions. Hence, a detailed study on the molecular pathways that cause NED and the role of this phenomenon in therapy resistance will be needed to improve treatment outcomes in prostate cancer. This review delineates the role of NED in mediating therapy resistance in prostate cancer and evaluates current therapeutic interventions, with the aim of informing the development of new treatment strategies for this malignancy.